Introducing the Concept of Population and the Indonesian Government System to Elementary Madrasah Students - Nur Fahisyah; Namiroh Lubis (Journal of Contemporary Islamic Primary Education, 2025)
This study aims to explore the initial understanding of elementary school (MI) students regarding the concept of population and the Indonesian government system, and to assess the effect of using contextual learning media in improving this understanding. The main issues raised are how MI students understand these abstract concepts and the extent to which contextual media can help facilitate deeper understanding. This study uses a qualitative approach with a descriptive study design, involving observation, interviews, and documentation in several MIs in Kendari City. The research informants consisted of students, teachers, and principals. The results of the study indicate that although students have basic knowledge about the population and the Indonesian government system, their understanding is still limited to factual and theoretical aspects. The use of contextual media that is relevant to students' daily lives can improve their understanding, making these concepts easier to understand and accept. As a result, contextual media has been shown to increase student engagement in learning and help them relate the material to their social lives, introducing citizenship values ​​more effectively. This study suggests the use of more diverse media and further research with larger samples to deepen understanding of the implementation of contextual learning in elementary school.